INSTAGRAM SOCIAL MEDIA COMMUNICATION STRATEGY IN MOTORCYCLE SALES MARKETING THROUGH ADIRA FINANCE LEASING - Farhat Kamal Pristiyadi,; Arvin Hardian,; Muhamad Khadafi Firman, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This research is motivated by the rapid development of social media that changes marketing communication patterns, including in the motor vehicle financing industry. Adira Finance, one of the largest leasing companies in Indonesia, utilizes the Instagram account @adirafinance to introduce motorcycle financing products to digital consumers. The purpose of this study is to analyze the communication strategies applied to Instagram content and measure their effectiveness based on the AIDA (Attention, Interest, Desire, Action) theory. The study used a descriptive qualitative approach with data collection through in-depth interviews, content observation, and social media archive documentation, which was then validated by data triangulation. The results show that Adira Finance's communication strategy is regularly structured through creative visual content, educational captions, customer testimonials, low installment promotions, and clear calls to action (CTAs). The use of interactive Instagram features such as reels, stories, polls, and direct messages has been proven to increase engagement and expand the reach of messages. The selection of broadcast hours and segmentation of the productive age audience also strengthen the strategy's effectiveness. In conclusion, Instagram-based marketing communications are effective in increasing interest, building trust, and encouraging real consumer action towards motorcycle financing services.